Zósimo: polémica religiosa y conflicto social - Plácido Suárez, Domingo (Antigüedad y Cristianismo, 1991)
This study is a valuation of the works of Zosimo, a direct witness of the ideological conflicts between the paganism a n d Christianity of his times, but from the special perspective of a pagan living in the Eastern Roman Empire . An analysis of the actuation of Zosimo in the religious controversies with the intention of proving the superiority of the pagan tradition. The subject is directly related with other great problems of this period, such as the presence of the barbarians in the Empireand the enormous diferences between the Easternan d Western parts of the Empire , both of which set the scene for the configuration of the European Medieval.